A new Quaternary stratigraphy of the Kallang River Basin, Singapore: Implications for urban development and geotechnical engineering in Singapore. (15th September 2020) - Chua, Stephen; Switzer, Adam D.; Kearsey, Timothy I.; Bird, Michael I.; Rowe, Cassandra; Chiam, Kiefer; Horton, Benjamin P.
Highlights: 161 boreholes were used to create a 3D geological model of the Kallang River Basin, Singapore. Two marine clay sequences, deposited during MIS 5e and the early Holocene, were observed for Singapore. This model reveals new complexities deposited during marine transgression and regression phases. A new stratigraphic framework and nomenclature for the wider Singapore is presented. Abstract: The Quaternary stratigraphy of many coastal areas in Southeast Asia is poorly understood. Developing a detailed framework is important as many coastal cities are built on these unconsolidated coastal-marine sediments. This study reviews the current understanding of Quaternary deposits in the Kallang River Basin, Singapore, using 161 boreholes to create 14 cross-sections and a 3D geological model. The dataset is augmented with a ~38.5 m long sediment core obtained from Marina South (1.2726°N, 103.8653°E), and a previous record from Geylang (1.3137°N; 103.8917°E), to provide age constraints and stratigraphic reference. A new Quaternary stratigraphic framework for Singapore is presented here, constrained by new radiocarbon and Optically Stimulated Luminescence (OSL) dating, and identify palaeo-features that record the geomorphic and sedimentary evolution of the basin. Fluvial deposits of Pleistocene age are uncomfortably overlain by littoral/tidal sands and subsequently marine clay possibly during Marine Isotope Stage (MIS) 5e (~125 ka BP). Subsequent subaerial exposure and weathering of the marine clay during the last interglacial produced a 'stiff clay' layer. The stiff clay is unconformably overlain by Holocene transgressive sands and peats from ~9.5 ka BP, followed by marine clays with a maximum basal age of ~9.2 ka BP. Regressive sandy/peat units were subsequently deposited beginning ~6 ka BP. Here the new Quaternary stratigraphic framework for Singapore is presented, as well as provide important constraints on the regional sea-level history and geomorphological evolution of Singapore's southern coast from MIS 5e to present. The work also highlights the complexities of geoengineering work in such subsurface terranes.